Technique of experimental measurements of the optical thickness of a pulse discharge plasma channel in water on a contour reabsorption lines of hydrogen Hα - O. A. Fedorovich (Âderna Fìzika ta Energetika, 2010)
In this work the results of development and application of the technique of experimental definition of optical thickness (τ) of the pulse discharge plasma channel in water which are based on the distribution of radiation intensities on contour reabsorption lines of hydrogen Ha (656.3 nm) are given. Optical thickness of continues spectrum was defined by extrapolation of intensities in far wing of contour reabsorption lines of hydrogen Ha, where t value did not vary any more, and the line smoothly transferred in continuous spectrum. The atomic concentration Na, received on a method of definition of t on a contour reabsorption lines of hydrogen Ha., agreed with calculation obtained from the equation of the plasma state. The recommendations on the correct definition of optical thickness of plasma of pulse discharge in liquids are given.